IMPLEMENTASI PROGRAM BIMBINGAN SOSIAL DALAM MENGATASI STRESS AKADEMIK MAHASISWA SELAMA PEMBELAJARAN DARING PADA PROGRAM STUDI PENDIDIKAN MASYARAKAT - Fauzi Kurniawan; Nurlaila Nurlaila; Friska Indria Nora Harahap; Jubaidah Hasibuan (Journal Education for All : Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2020)
This study aims to determine the effect of social guidance programs in dealing with student academic stress during online learning in community education study programs. The problem in this research is that the situation and conditions are full of pressure and the many demands can be a stressor which is quite influential on the academic performance of students in participating in learning. Given the current conditions that require students to study online due to the spread of the Covid-19 virus, resulting in a global pandemic throughout Indonesia. This type of research is a quasi-experimental, by taking the subject through random sampling techniques on community education students. The data collection technique was carried out through a questionnaire. Before the implementation of social guidance, researchers conducted a pretest on the subject in order to find out how much the student's academic stress level was through a validity-tested questionnaire with an average value of 94.27, then carried out a schedule of social guidance activities according to the material that had been designed, namely 4 times of guidance with a duration of time. 120 minutes, finally do a posttest with the same questionnaire to see changes in student academic stress levels after social guidance with an average value of 63.18.